GAMBARAN PENGETAHUAN ODHA TENTANG PENULARAN HIV/AIDS - Rasyidah " "; Sri " Utami; Yufitriana " Amir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractAIDS have symptoms caused by the HIV virus. It is contagious. The viruses damage the immune system. HIV will develope to AIDS stage for approximately 7-10 years after HIV transmission,the aim of this study todescribe knowledge of people living with HIV in Puskesmas Dumai City. The study design is simple descriptive with 34 respondents taken bypurposife sampling. The instrument used in this study was a questionnaire“knowledge of HIV transmission". The results of this study are a good knowledge (47,1%) insufficient knowledge (41,2%) and lack of knowledge (11,8%). It is expected that health centers provide more information about HIV prevention in order to reduce HIV transmission to others and could develop this research further. Keywords                  : HIV, HIV tranmission, knowledge